Respect For The Red White Flag in The Understanding of Syataryah and Muhammadiyah Communities: A Comparative Study - Edriagus Saputra; Gusnanda Gusnanda; Nana Gustianda; Wisda Rahmadinur; Amal Syahidin (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The aims of this study was to gain an understanding of the Syatariyah tariqat community and the Muhammadiyah Organization regarding respect for the red and white flag. In this study, the author uses a qualitative method (field research) with a comparative approach (compare). In this study, the respondents were cadres and communities connected to the Syatariyah tariqat and Muhammadiyah organizations. This study found that the opinion of the Syatariyah and Muhammadiyah people regarding respect for the Red and White Flag is something that must be done as an Indonesian citizen. Because the respect that the people show for the flag is a form of love for the State of Indonesia and remembers the struggle of the nation's heroes in expelling the colonialists and liberating their country. In addition, the respect done to the Red and White Flag is a form of ta'zim (glorification) not in the form of ta'abud (worship). Then, the values contained in respect for the Red and White Flag have the most important things for the Indonesian people, namely the Value of Commemorating the History of the Struggle, Nationalist Values, telorance Values, and the Value of Unifying the Nation.